Approach for energy diagnostic of intermediate municipalities in Colombia - Bermejo, Fabio; Cabello, Juan; Sagastume, Alexis; Mendoza, Jorge; Rueda-Bayona, Juan (Frontiers in Sustainable Cities, 2025)
The article focuses on developing a methodology for energy diagnostics in intermediate Colombian municipalities as an initial stage for implementing a Municipal Energy Management System. The study is conducted in the municipality of Sabanalarga during the period from 2010 to 2022. The methodology consists of four key steps: the socioeconomic characterization, energetic supply-side analysis, energetic demand-side analysis, and assessment of energy performance indicators for effective energy planning. The results indicate that, although agriculture is the primary driver of the local economy, the transportation and residential sectors are the largest energy consumers. Lower-income residents, who have limited access to modern energy services, consume less electricity per capita compared to higher-income residents. In rural areas, lower-income households primarily rely on firewood for cooking. Additionally, due to the low level of industrialization, both energy and power intensity fall below the national average. To support municipal authorities in making informed decisions, the development of a municipal energy management system is essential.